Meditation in Educational Places as a Protective Factor Against Violence - Randazzo-Eisemann, Francesca (Revista Electrónica Educare, 2021)
Introduction. This article explores the impact that meditation has on education as a protective factor against violence. The aim is to determine how meditation promotes the development of peace culture in educational centers, and to demonstrate its positive correlation in the education quality. The objective is to clarify whether meditating can favor school environments of peaceful coexistence and conflict resolution contributing to improve the performance and achievements of the school attendants, as well as promoting greater well-being for the rest of the educational community members. Methods. This is an exploratory qualitative-quantitative constructionist study, based on interviews and questionnaires applied to agents involved in the social process: students, teachers, and volunteers facilitating the meditation technique. Results. According to their perception, it is concluded that meditation in educational contexts promotes protective factors against violence, such as patience, sensitivity, emotional balance, well-being, and relaxation. By having calm and harmony, the levels of stress, aggressiveness, anxiety, and impulsivity decrease. It makes people less conflictive, more pleasant, understanding, respectful, sociable, promoting peaceful coexistence. It improves mood and self-esteem. This allows better social interaction: more and better peer relationships, acceptance, respect, collaboration, support, solidarity, and integration.